Spectral and High Order Methods for Partial Differential Equations Selected papers from the ICOSAHOM '09 conference, June 22-26, Trondheim, Norway - Hesthaven, Jan S.; Rønquist, Einar M. (Lecture Notes in Computational Science and Engineering,, 2011)
The book contains a selection of high quality papers, chosen among the best presentations during the International Conference on Spectral and High-Order Methods (2009), and provides an overview of the depth and breadth of the activities within this important research area. The carefully reviewed selection of the papers will provide the reader with a snapshot of state-of-the-art and help initiate new research directions through the extensive bibliography.